The Role of Echocardiography in the Evaluation of AHF - Rizzo, Toni (MD Conference Express, 2014)
Timely evaluation of patients presenting with symptoms of acute heart failure is crucial to making a prompt diagnosis and selecting appropriate therapeutic measures. Using echocardiography, the clinician can quickly and noninvasively obtain information about the causal condition, critical hemodynamic factors, and the etiology of lung congestion.